2004
DOI: 10.4102/ac.v4i1.54
|View full text |Cite
|
Sign up to set email alerts
|

The supervision of research for dissertations and theses

Abstract: South African higher institutions of learning are engaged in rapid transformation processes. Some of the consequences are that an increasing proportion of the postgraduate student body is from previously disadvantaged backgrounds and that the body of academic staff has also been transformed. In general, students have limited experience of independent research work as well as using library and other research facilities. However, quality research needs to be maintained. It is of great importance that academics s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…Many graduate students are mature and/or distance learners with needs different to those of residential and undergraduate students (Humphrey and McCarthey, 1999). Part-time students struggle to cope with their simultaneous academic and professional workloads and experienced a lack of support and understanding from their supervisors, inflexible program organization and structures, and a feeling of isolation (Lessing and Lessing, 2004;Mackinnon, 2004). Graduate students report anxiety as a result of uncertainty about what is expected of them and procedures such as assessment (Lovitts, 2005;Malfroy, 2005).…”
Section: General Overview Of Postgraduate Research Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Many graduate students are mature and/or distance learners with needs different to those of residential and undergraduate students (Humphrey and McCarthey, 1999). Part-time students struggle to cope with their simultaneous academic and professional workloads and experienced a lack of support and understanding from their supervisors, inflexible program organization and structures, and a feeling of isolation (Lessing and Lessing, 2004;Mackinnon, 2004). Graduate students report anxiety as a result of uncertainty about what is expected of them and procedures such as assessment (Lovitts, 2005;Malfroy, 2005).…”
Section: General Overview Of Postgraduate Research Studiesmentioning
confidence: 99%
“…These findings indicate that a differentiated approach to providing information and support to graduate students may be necessary. Lessing and Lessing (2004) add that there needs to be a balance between supervisor input and student independence. Lesssing and Schulze (2002) describe the supervisory role as a balancing act between various factors: expertise in the area of research, support for the student, critique, and creativity.…”
Section: The Responsibilities Of Supervisormentioning
confidence: 99%
“…To address this issue, several studies have been conducted on the factors associated with the successful and timely study completion of students in research programs (i.e., Latona & Browne, 2001;Lessing & Lessing, 2004). Latona and Browne (2001) developed a framework that defines three factors that can influence the timely study completion of students.…”
Section: Postgraduate Tracking System (Postracker)mentioning
confidence: 99%
“…These three factors are institutional or environmental factors, individual supervision arrangements, and certain student characteristics. In another study, Lessing and Lessing (2004) identified several factors that may influence the graduation time of students; these factors include student-friendly environment at the institution, excellent administrative support from the faculty, strict entry requirements for entrants, and support from supervisors. Tinto (2004) posited that increasing student retention and graduation is possible and recommended the implementation of a mechanism to monitor student progress and performance.…”
Section: Postgraduate Tracking System (Postracker)mentioning
confidence: 99%
“…To mention a few of them here as follows : Cadman, 2000;Grant, 2003;Ho, Wong & Wong, 2010;Lessing & Lessing, 2004;Sadeghi & Khajepha , 2015;Strauss, 2012;Wang & Li, 2008, 2011. Since these studies are intended for master and PhD students' thesis writing problems, in some contexts they are different from what we have done in terms of their purposes and problems being highlighted.…”
Section: Introductionmentioning
confidence: 99%